Work process of nursing professors - Denisse Parra Giordano; Vanda Elisa Andres Felli (Universidade de São Paulo, 2017)
ABSTRACT Objective: to analyze the work process of nursing professors. Method: descriptive, exploratory and qualitative study, developed with a focus on critical epidemiology, carried out at a School of Nursing in Chile. The research subjects consist of 17 nursing professors, with whom individual semi-structured interviews were carried out and nine participated in a focus group. The Ethics Committee approved this study. Results: 88.2% were female, mean age of 42 years, 47% were married, 94% were Chilean, average length of service in the institution of 2.8 years, and 23.5% had a master's degree. Regarding the work process, the students were the work object, the tools used were the knowledge and the experience as a nurse, and the work environment was considered good. Regarding the form of work organization, 76% have a 44-hour workweek, the wage was considered inadequate and the workload was higher than foreseen in the contract. The dialectic of the nursing work process is evidenced, demonstrating the contradiction between the low wages and labor overload and the narratives reporting a good work environment, personal fulfillment and transcendence that goes far beyond work. Conclusions: the work process allows describing the work components of the nursing professors, which are consistent with the results of the literature and show the dialectic of the nursing work process.